Adolescent digital profiles: A process-based typology of highly engaged internet users - Tzavela, E.C.; Karakitsou, C.; Halapi, E.; Tsitsika, A.K. (2017)
High online engagement is common among adolescents. Besides concerns, not all highly involved adolescents online develop maladaptive patterns of use. The focus of the present qualitative study was to explore the experiences of highly engaged adolescents with signs of internet addictive behaviors. We aimed to uncover the processes differentiating high online engagement, and formulate a typology of users. Semi-structured individual interviews were conducted with 72 adolescents (Mage = 15.7 years; SD = 0.6) living in Greece, Spain, Iceland and Poland. Interviews were analyzed using grounded theory. A typology of highly engaged adolescents emerged based on three processes: satisfying needs across contexts (online-offline), experiencing personal gains and losses and self-regulating use. Four distinct user profiles emerged, ranging from adaptive (Juggling it All, Coming Full Cycle) to maladaptive (Stuck Online, Killing Boredom). The developed typology can help parents, teachers and professionals better understand the ways high engagement is experienced within a developmental context. Such knowledge can inform the development of prevention and supportive services. Implications for assessment and intervention are discussed for each profile. © 2016 Elsevier Ltd